Pfas adsorbent, and method for producing pfas adsorbent

JP2025042543AActive Publication Date: 2025-03-27UBE CHEM IND CO LTD

Patent Information

Application Number
JP2023149633
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-14
Publication Date
2025-03-27
Estimated Expiration
2043-09-14

Smart Images

  • Figure 2025042543000001
    Figure 2025042543000001
Patent Text Reader

Abstract

To provide a novel absorbent for perfluoroalkyl compounds and polyfluoroalkyl compounds, wherein the absorbent does not contain much carbon material such as activated carbon.SOLUTION: An absorbent for perfluoroalkyl compounds and polyfluoroalkyl compounds comprises a porous body containing magnesium oxide and aluminum oxide. The content of magnesium oxide exceeds 9 mass%.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a PFAS adsorbent and a method for producing the PFAS adsorbent. [Background technology]

[0002] In recent years, environmental pollution caused by organic fluorine compounds (PFASs: per- and polyfluoroalkyl substances, their salts, and their derivatives) has become a problem. In particular, perfluorooctanoic acid (PFOA) and perfluorooctanesulfonic acid (PFOS) among PFASs are highly toxic. These organic fluorine compounds are known as persistent organic pollutants.

[0003] It is known that inexpensive activated carbon is used to remove persistent organic pollutants from contaminated water. The following Patent Document 1 discloses an adsorbent having a carbon material such as activated carbon containing calcium or magnesium. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Special Publication No. 2022-526606 Summary of the Invention [Problem to be solved by the invention]

[0005] However, the adsorbents described in the prior art are mainly made of activated carbon, and such adsorbents containing activated carbon must be incinerated at high temperatures for disposal after adsorption of PFAS, which can generate large amounts of carbon dioxide during disposal.

[0006] Therefore, there is a need for an adsorbent for perfluoroalkyl and polyfluoroalkyl compounds having a novel composition that does not contain activated carbon that generates carbon dioxide. [Means for solving the problem]

[0007] The adsorbent for perfluoroalkyl and polyfluoroalkyl compounds according to one embodiment contains a porous body containing magnesium oxide and aluminum oxide, the magnesium oxide content being greater than 9 mass %.

[0008] A method for producing an adsorbent for perfluoroalkyl and polyfluoroalkyl compounds according to one embodiment includes the steps of mixing a magnesium oxide precursor, an aluminum oxide precursor, and water, granulating the mixture, and calcining the granules. Effect of the Invention

[0009] According to the above embodiment, it is possible to provide an adsorbent for perfluoroalkyl and polyfluoroalkyl compounds having a novel composition. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] It should be noted that the present disclosure is not limited to the particular devices and methods described. The terminology used in the present disclosure is for the purpose of describing particular embodiments or examples and is not intended to limit the scope of the claims.

[0011] The adsorbent according to one embodiment is for adsorbing organic fluorine compounds, preferably PFAS (perfluoroalkyl compounds, polyfluoroalkyl compounds, their salts, and their derivatives). In this specification, the adsorbent for adsorbing PFAS is referred to as a PFAS adsorbent. However, hereinafter, for simplicity, the PFAS adsorbent is also simply referred to as an "adsorbent".

[0012] Examples of PFAS include perfluoroalkyl sulfonates, perfluoroalkanesulfonic acids (PFSA), N-butylperfluoroalkanesulfonamides (BuFASA), N-butylperfluoroalkanesulfonamideethanol (BuFASE), N-butylperfluoroalkanesulfonamideacetic acid (BuFASAA), N-ethylperfluoroalkanesulfonamides (EtFASA), N-ethylperfluoroalkanesulfonamideethanol (EtFASE), N-ethylperfluoroalkanesulfonamideacetic acid (EtFASAA), perfluoroalkanesulfonamides (FASA), perfluoroalkanesulfonamideethanol (FASE), perfluoroalkanesulfonamideacetic acid (FASAA), N-methylperfluoroalkanesulfonamides (Methylperfluoroalkanesulfonamides ... Perfluoroalkanesulfonamide sulfonyl fluoride (PASF), 4,8-dioxa-3H-perfluorononanoic acid, ammonium perfluorooctanoate (APFO), fluoroproteins (FP), fluorotelomer carboxylic acid (FTCA), fluorotelomer alcohol (FTOH), fluorotelomer sulfonate (FTS), fluorotelomer sulfonic acid (FTSA), perfluoroalkyl acid (PFAA), perfluoroalkylsulfonamidoethanol (PFOSE), and any derivatives thereof. This includes, for example, perfluorooctanoic acid (PFOA), perfluorooctane sulfonate, perfluorooctane sulfonic acid (PFOS), 2,3,3,3-tetrafluoro-2-(heptafluoropropoxy)propanoate, ammonium 2,3,3,3-tetrafluoroethyl-2-(heptafluoropropoxy)propanoate, 1,2,2,2-Tetrafluoroethyl ether, 4:2-fluorotelomer sulfonic acid (4:2 FtS), 6:2-fluorotelomer sulfonic acid (6:2 FtS), 8:2-fluorotelomer sulfonic acid (8:2 FtS), perfluorobutanoic acid (PFBA), perfluorobutane sulfonate, perfluorobutane sulfonic acid (PFBS), perfluorohexane sulfonate, perfluorohexane sulfonate (PFHxS), perfluorohexanoate, perfluorohexanoic acid (PFHxA), 4,8-Dioxa-3H-perfluorononanoic acid, Ammonium perfluorooctanoate (APFO), N-Ethyl perfluorooctanesulfonamide (EtFOSA), N-Ethyl perfluorooctanesulfonamidoethanol (EtFOSE), Perfluorooctanesulfonamide (PFOSA), Perfluorooctanesulfonamidoacetic acid (FOSAA), Perfluorooctanesulfonamidoethanol (FOSE), Perfluorobutanoate, Perfluorobutanoic acid, Perfluorobutyrate, Perfluorobutyric acid, Perfluoroalkyl carboxylate, Perfluoroalkyl carboxylate (PFCA), Perfluorodecanoate, Perfluorodecanoic acid (PFDA), Perfluorododecanoate, Perfluorododecanoic acid (PFDoA), Perfluorododecanesulfonate (PFDoS), Perfluorododecanesulfonic acid (PFDoSA), Perfluorodecanesulfonate, Perfluorodecanesulfonic acid (PFDS), Perfluoroheptanesulfonate, Perfluorohept ... perfluoropentanoate, perfluoroheptanoic acid (PFHpA), perfluoroheptanesulfonate, perfluoroheptanesulfonic acid (PFHpS), perfluorononanoate, perfluorononanoic acid (PFNA), perfluorononanesulfonate, perfluorononanesulfonic acid (PFNS), perfluorooctanoic acid, perfluorophosphonic acid (PFPA), perfluoropentanoate, perfluoropentanoic acid (PFPeA), perfluoropentanesulfonate, perfluoropentanesulfonic acid (PFPeS), perfluorophosphinic acid (PFpiA), perfluorotetradecanoic acid (PFTeDA), perfluorotridecanoic acid (PFTrDA), perfluoroundecanoate, perfluoroundecanoic acid (PFUnA), perfluoroundecanesulfonate (PFUnS), perfluoroundecanesulfonic acid (PFUnSA), polytetrafluoroethylene (PTFE), or 8:2 fluorotelomer alcohol (8:2FTOH). ,

[0013] The adsorbent for perfluoroalkyl and polyfluoroalkyl compounds may be one that adsorbs at least one of the PFASs listed above. The adsorbent may be for adsorbing PFASs having a composition with a carbon number of 3 to 18, preferably 4 to 14, more preferably 6 to 10, and even more preferably 8. The adsorbent may be for adsorbing at least one of PFOA and PFOS, which have a carbon number of 8, for example.

[0014] The adsorbent has a porous body containing magnesium oxide, and the porous body preferably contains magnesium oxide and aluminum oxide, or is preferably made of magnesium oxide.

[0015] The content of magnesium oxide in the entire adsorbent may be 9% by mass or more, preferably more than 9% by mass, more preferably 15% by mass or more, and even more preferably 20% by mass or more, and may be 100% by mass or less.

[0016] The sum of the pore volume Vp(BJH) of the adsorbent (porous body) calculated by the BJH method and the pore volume Vp(MP) of the adsorbent (porous body) calculated by the MP method may be 0.40 mL / g or more and 2.00 mL / g or less. The sum of Vp(BJH) and Vp(MP) is preferably 0.50 mL / g or more and 1.40 mL / g or less, more preferably 0.60 mL / g or more and 1.00 mL / g or less, and even more preferably 0.68 mL / g or more and 0.84 mL / g or less.

[0017] In this specification, the pore volume Vp(BJH) of the adsorbent calculated by the BJH method and the pore volume Vp(MP) of the adsorbent (porous body) calculated by the MP method are calculated by analyzing nitrogen adsorption isotherms.

[0018] From the viewpoint of PFAS adsorption, for the adsorbent (porous body), the ratio of Vp(BJH) to the sum of the pore volume Vp(BJH) calculated by the BJH method and the pore volume Vp(MP) calculated by the MP method may be 50% or more, preferably 55% or more, and more preferably 60% or more.

[0019] The lower limit of Vp(BJH) may be 0.20mL / g or more, preferably 0.30mL / g or more, more preferably 0.40mL / g or more. The upper limit of Vp(BJH) is not particularly limited, but may be 1.80mL / g or less, 1.60mL / g or less, 1.10mL / g or less, or 0.60mL / g or less. However, Vp(BJH) may be within a range that combines any of the above upper and lower limits.

[0020] The BET specific surface area of ​​the adsorbent is 50m 2 / g or more, 100m 2 / g or more, or 150m 2 / g or more. It is believed that the higher the BET specific surface area of ​​the adsorbent, the higher the adsorption capacity of the adsorbent for PFAS.

[0021] The upper limit of the BET specific surface area of ​​the adsorbent is 800m 2 / g or less, 500m 2 / g or less, 400m 2 / g or less, 375m 2 / g or less or 360m 2 / g or less.

[0022] The BET specific surface area can be measured by a BET multipoint method.

[0023] The pore volume (Vp(MP) and Vp(BJH)) and BET specific surface area described above can be changed by the magnesium oxide content, the hydration time or firing time described below, and the temperature during hydration or firing.

[0024] The adsorbent may contain aluminum oxide as described above. Preferably, the aluminum oxide may be formed by hydrating and hardening hydraulic alumina and then calcining the resultant. By using such aluminum oxide, a porous body having the above-mentioned pore volume and BET specific surface area and containing magnesium oxide can be easily produced.

[0025] The adsorbent may have the form of a porous molded body (filter). The adsorbent having the form of a porous molded body can maintain its shape in a solution, and can be used as a filter that can be easily recovered. The adsorbent may have the form of a porous powder.

[0026] When the adsorbent is in the form of a porous molded body (filter material), the adsorbent can be used while maintaining its shape without disintegrating in water. On the other hand, when the adsorbent is in the form of a powder, the adsorbent can be used by dispersing it in water. In addition, it is preferable that the porous body does not substantially contain a carbon material such as activated carbon. This can prevent a large amount of carbon dioxide from being generated by incineration when the adsorbent is disposed of.

[0027] When the adsorbent has the form of a porous molded body, the shape of the porous molded body is not particularly limited. The shape of the porous molded body may be, for example, a sphere, an ellipsoid, a cylinder, a rectangular column, a honeycomb, etc. The size of the porous molded body, specifically the length (maximum length) of the longest part of the porous molded body, is not particularly limited, but may be 0.5 mm or more, preferably 1 mm or more, more preferably 3 mm or more, and even more preferably 5 mm or more.

[0028] [Method of manufacturing the adsorbent] First, a step of mixing at least magnesium oxide precursor and water and granulating to form a granulated product (granulation step) is carried out. The magnesium oxide precursor may contain magnesium hydroxide, magnesium oxide, basic magnesium carbonate, normal magnesium carbonate, anhydrous magnesium carbonate, or at least one of these salts. The aluminum oxide precursor may contain aluminum hydroxide, aluminum oxide, aluminum carbonate, or at least one of these salts.

[0029] When the adsorbent to be produced is composed of magnesium oxide alone and does not contain aluminum oxide, the granulation step is performed by mixing a magnesium oxide precursor with water and granulating the mixture. In this case, the purity of the magnesium oxide precursor may be 95% by mass or more.

[0030] When the adsorbent to be produced contains aluminum oxide, in the granulation step, the granules are formed by mixing a magnesium oxide precursor, an aluminum oxide precursor and water, and granulating the mixture.

[0031] Hydraulic alumina can be used as the aluminum oxide precursor. When hydraulic alumina is used, it can be hardened by hydration when mixed with water, making it easy to produce a porous body of a desired shape.

[0032] In the granulation step, the magnesium oxide precursor is mixed so that the magnesium oxide content after firing described below is 9 mass% or more, preferably more than 9 mass%, more preferably 15 mass%, and even more preferably 20 mass% or more. The magnesium oxide content is a value excluding volatile components such as water contained in the granules.

[0033] When the adsorbent to be produced is made of magnesium oxide, the granules are formed by mixing only magnesium oxide precursor and water, followed by granulation.

[0034] In the granulation step, it is preferable that water is added dropwise while being mixed in. The granulation method is not particularly limited, but extrusion granulation, rolling granulation, or any other arbitrary granulation method can be used.

[0035] Preferably, the granulated material formed in the granulation step is exposed to water vapor to further hydrate and harden the granulated material (steaming step). The granulated material can be exposed to water vapor by being placed in a sealed container filled with water so as not to be immersed in water. In this case, the temperature in the sealed container may be in the range of 25°C to 150°C. The time for which the granulated material is exposed to water vapor in the sealed container (hydration time) may be in the range of 0.5 hours to 36 hours.

[0036] In the above-mentioned granulation process, the physical properties, hardness, etc. of the granulated material may vary depending on the temperature and humidity of the atmosphere. By carrying out the above-mentioned seasoning process, such variations can be eliminated. After the seasoning process, a drying process for drying the granulated material may be carried out.

[0037] Next, a step of calcining the granulated material (calcination step) is carried out. This forms a porous body (adsorbent) containing magnesium oxide and aluminum oxide, or a porous body made of magnesium oxide alone. The calcination temperature may be in the range of 300°C to 800°C. The calcination time may be in the range of 0.5 hours to 18 hours. The calcination can be carried out in an air atmosphere, a nitrogen atmosphere, or in a vacuum using a calcination furnace.

[0038] The porous body made of magnesium oxide alone is produced in the form of a powder after the firing process. The porous body made of magnesium oxide alone may remain in the form of a powder, or may be formed into a filter material using any binder. On the other hand, the porous body containing magnesium oxide and aluminum oxide is produced in a state in which the granulated form is maintained after the firing process. Therefore, the porous body containing magnesium oxide and aluminum oxide is easily formed into a filter material having a specific shape.

[0039] The above-mentioned adsorbent can be produced by the above-mentioned steps. Here, the pore volume (Vp(MP) and Vp(BJH)) and BET specific surface area of ​​the porous body (adsorbent) can be adjusted by the magnesium oxide content, the above-mentioned hydration time or firing time, the temperature during hydration or firing, and the physical properties of the aluminum oxide precursor.

[0040] [Example] Hereinafter, examples will be described in detail, but it should be noted that the present invention is not limited to the aspects described in the following examples.

[0041] [Example 1] A mixture of 50 g of hydraulic alumina (Sumitomo Chemical: BK-112) and 7.23 g of magnesium hydroxide (Ube Materials: UD-650) was placed in a SUS container, and the container was set on a rotating table for a ball mill. The ball mill was tilted at a certain angle and rotated at 300 rpm, while 24 g of water was dropped to form a granulated material (granulation process). Next, the granulated material was placed in a sealed container, and water was poured into the sealed container so that the granulated material would not come into contact with the water, and the granulated material was hardened while being hydrated at 80°C for 16 hours (steaming process). The hardened granulated material was dried at 100°C for 3 hours, and then the granulated material was fired in an electric furnace at 380°C for 3 hours to produce a porous body (adsorbent) (firing process). The magnesium oxide content in the porous body was 9.1% by mass.

[0042] [Example 2] A porous body (adsorbent) was produced in the same manner as in Example 1, except that the amount of magnesium hydroxide (UD-650 manufactured by Ube Material Industries, Ltd.) was changed to 21.69 g and the amount of water was changed to 28 g. The magnesium oxide content in the porous body was 23 mass%.

[0043] [Example 3] A porous body (adsorbent) was produced in the same manner as in Example 1, except that the amount of hydraulic alumina (Sumitomo Chemical: BK-112) was changed to 25 g, the amount of magnesium hydroxide to 36.15 g, and the amount of water to 22 g. The magnesium oxide content in the porous body was 50 mass%.

[0044] [Example 4] 50 g of magnesium hydroxide (UD-650, manufactured by Ube Materials) was placed in a stainless steel container, and the container was set on a rotating table for a ball mill. The ball mill was tilted at a certain angle and rotated at 300 rpm, while 19 g of water was dropped and granulated to form a granulated material (granulation process). Next, the granulated material was placed in an airtight container, which was filled with water so that the granulated material would not come into contact with the water, and hydrated at 80°C for 16 hours (steaming process). The granulated material was fired in an electric furnace at 380°C for 3 hours to produce a porous body (adsorbent) (firing process). The porous body was made of magnesium oxide alone.

[0045] [Reference example 1] Activated carbon (manufactured by UES, UCG-AG) was prepared as an adsorbent.

[0046] For the above Examples 1 to 4 and Reference Example 1, the BET specific surface area (S BET ), Vp(MP), Vp(BJH), the sum of Vp(MP) and Vp(BJH), and the ratio of Vp(BJH) to the sum of Vp(MP) and Vp(BJH) are measured and are shown below in Table 1. These measurements can be performed as follows.

[0047] Vp(MP) and Vp(BJH) were calculated by analyzing the nitrogen adsorption isotherm. Specifically, first, about 30 mg of the adsorbent sample was weighed on a precision balance, and the sample was pretreated in a gas adsorption amount measuring device (BELSORP-miniX: manufactured by Microtrack Bell) under a nitrogen atmosphere at 200°C for 10 minutes, and then the nitrogen adsorption isotherm was measured by the gas adsorption amount measuring device. Here, the purity of the nitrogen gas was 99.999% or more, the measurement temperature was 77K (liquid nitrogen temperature), and the measurement pressure was 0.0 to 101.3kPa (relative pressure P / P0 = 0.0 to 1.0).

[0048] Vp(MP) was calculated from the adsorption isotherm (BELMASTER TM 7) was used to calculate the integrated value of the pore size distribution of the sample using the MP method.

[0049] Vp(BJH) was calculated from the adsorption isotherm (BELMASTER TM 7) was used to calculate the integrated value of the pore size distribution of the sample using the BJH method.

[0050] The BET specific surface area was measured by pretreatment at 200° C. for 10 minutes and then by the nitrogen gas adsorption method using a Tristar II 3020 (Shimadzu Corporation) with a BET multipoint method.

[0051] The sum of the pore volume Vp(BJH) calculated by the BJH method and the pore volume Vp(MP) of the adsorbent (porous body) calculated by the MP method for the adsorbents according to Examples 1 to 4 is 0.40 mL / g or more. In particular, the sum of Vp(BJH) and Vp(MP) for the adsorbents according to Examples 2 and 3 is greater than the sum of Vp(BJH) and Vp(MP) for the adsorbent according to Reference Example 1.

[0052] In addition, in Examples 1 to 4, the ratio of Vp(BJH) to the total value of Vp(MP) and Vp(BJH) (hereinafter simply referred to as "Vp(BJH) ratio") is 50% or more. The Vp(BJH) ratios in Examples 1 to 4 are higher than the Vp(BJH) ratio in Reference Example 1.

[0053] [Table 1] JPEG2025042543000001.jpg37155

[0054] [Adsorption experiment] Three kinds of aqueous solutions containing PFOS (potassium perfluorooctane sulfonate, Fujifilm Corporation, product code: 009151) with different concentrations were prepared. The initial concentrations of PFOS in each aqueous solution were 300 mg / L, 25 μg / L, and 100 ng / L, respectively. The adsorbents according to Examples 1 to 4 were added to the aqueous solutions so that the amount of each adsorbent was 1000 mg / L, and the solutions were stirred at about 25° C. for 1 hour using a mini rotator. In Examples 1 to 4 and Reference Example 1, all the adsorbents were used after being powdered in a mortar. Then, the adsorbents were removed from the aqueous solutions using a syringe filter. The aqueous solutions from which the adsorbents had been removed were analyzed using a liquid chromatograph mass spectrometer (LC-MS / MS) to measure the concentration (X) of PFOS, and the removal rate was calculated using the formula (1-(X / initial concentration measurement))×100. The results of the removal rate of PFOS are shown in Table 1 below. In Reference Example 1, activated carbon was added to the aqueous solution containing PFOS so that the amount of activated carbon was 1000 mg / L, and an adsorption experiment was carried out in the same manner as in Examples 1-4.

[0055] In an adsorption experiment using an aqueous solution containing a high concentration of PFOS (initial concentration: 300 mg / L), it is clear from Table 1 that the greater the magnesium oxide content in the adsorbent, the higher the adsorption ability of the adsorbent tends to be. The adsorbent according to Example 1 has a removal rate for high concentrations of PFOS close to that of the activated carbon of Reference Example 1. Therefore, an adsorbent with an MgO content of 9 mass % can be used to remove high concentrations of PFOS, similar to activated carbon.

[0056] The adsorbents of Examples 2 and 4 have a higher removal rate for high-concentration PFOS than the activated carbon of Reference Example 1. Therefore, an adsorbent having an MgO content of more than 9 mass%, more preferably 15 mass% or more, is suitable for removing high-concentration PFOS.

[0057] In an adsorption experiment using an aqueous solution containing a medium concentration of PFOS (initial concentration: 25 μg / L), it is seen from Table 1 that the adsorbents of Examples 1 and 2 have a much higher adsorption capacity than the adsorbent of Reference Example 1. Therefore, an adsorbent made of a porous body containing magnesium oxide, more specifically a porous body containing magnesium oxide and aluminum oxide, can be suitably used to remove medium concentrations of PFOS.

[0058] Under normal circumstances, the concentration of PFOS in contaminated water is lower than 25 μg / L. Therefore, it is considered that the adsorbents in Examples 1 and 2 can exhibit sufficient PFOS adsorption effect. In addition, it is considered that the higher the magnesium oxide content, the higher the PFOS adsorption effect, so it is found that a porous body containing 9 mass % or more of magnesium oxide can be suitably used as a PFOS adsorbent.

[0059] In an adsorption experiment using an aqueous solution containing low concentrations of PFOS (initial concentration: 100 ng / L), it can be seen from Table 1 that when the magnesium oxide content in the adsorbent increases to a certain extent, the adsorption capacity of the adsorbent increases. Therefore, an adsorbent made of a porous body containing magnesium oxide can be suitably used to remove low concentrations of PFOS. An aqueous solution containing low concentrations of PFOS (initial concentration: 100 ng / L) can occur in the real environment. Therefore, an adsorbent made of a porous body containing magnesium oxide is considered to be practically usable as an adsorbent.

[0060] The adsorbents according to Examples 1 to 4 are considered to be applicable to the adsorption of PFAS, which is a compound of the same family as PFOS. The adsorbents according to Examples 1 to 4 can also be used to adsorb substances other than PFAS.

[0061] From the description of the above embodiments and / or examples, it should be noted that at least the inventions described in the following appendices are explicitly stated in this specification.

[0062] [Appendix 1] An adsorbent having a porous body containing magnesium oxide. [Appendix 2] 2. The adsorbent according to claim 1, wherein the magnesium oxide content is 9% by mass or more, preferably more than 9% by mass, more preferably 15% by mass or more. [Appendix 3] 3. The adsorbent according to claim 1 or 2, wherein the sum of the pore volume Vp(BJH) calculated by the BJH method and the pore volume Vp(MP) calculated by the MP method is 0.40 mL / g or more and 2.00 mL / g or less. [Appendix 4] An adsorbent according to any one of appendix 1 to 3, wherein the ratio of Vp(BJH) to the sum of the pore volume Vp(BJH) calculated by the BJH method and the pore volume Vp(MP) calculated by the MP method is 50% or more. [Appendix 5] 5. The adsorbent according to claim 3, wherein the porous body is made of magnesium oxide. [Appendix 6] 5. The adsorbent according to any one of claims 1 to 4, wherein the porous body contains magnesium oxide and aluminum oxide. [Appendix 7] 7. The adsorbent according to any one of claims 1 to 6, wherein the adsorbent is for adsorbing organofluorine compounds, preferably PFAS. [Appendix 8] An adsorption method comprising adsorbing an organic fluorine compound, preferably PFAS, using the adsorbent described in any one of appendixes 1 to 7. [Appendix 9] A method for producing an adsorbent, comprising: a granulation step of mixing at least a magnesium oxide precursor and water and granulating the mixture to form a granulated material; and a firing step of firing the granulated material. [Appendix 10] 10. The method for producing an adsorbent according to claim 9, wherein in the granulation step, the magnesium oxide precursor is mixed so that the magnesium oxide content after calcination is 9% by mass or more, preferably more than 9% by mass, more preferably 15% by mass or more. [Appendix 11] The method for producing an adsorbent according to claim 9 or 10, wherein the granules are formed by mixing a magnesium oxide precursor, an aluminum oxide precursor and water, and granulating the mixture. [Appendix 12] The method for producing an adsorbent according to claim 9 or 10, wherein the granules are formed by mixing substantially only magnesium oxide precursor and water, followed by granulation. [Appendix 13] 13. The method for producing an adsorbent according to any one of claims 9 to 12, wherein the magnesium oxide precursor comprises magnesium hydroxide, magnesium oxide, and at least one of basic magnesium carbonate, normal magnesium carbonate, anhydrous magnesium carbonate, and salts thereof. [Appendix 14] 14. The method of claim 9, wherein the aluminum oxide precursor comprises at least one of aluminum hydroxide, aluminum oxide, aluminum carbonate, and salts thereof, and preferably comprises hydraulic alumina.

[0063] As described above, the contents of the present invention have been disclosed through the embodiments and / or examples, but the description forming part of this disclosure should not be understood as limiting the present invention. From this disclosure, various alternative embodiments, examples and / or operating techniques will become apparent to those skilled in the art. Therefore, the technical scope of the present invention is defined only by the invention-specific matters related to the appropriate claims from the above description.

Claims

1. An adsorbent for perfluoroalkyl and polyfluoroalkyl compounds, comprising a porous body containing magnesium oxide and aluminum oxide, the magnesium oxide content of which exceeds 9 mass %.

2. The adsorbent for perfluoroalkyl and polyfluoroalkyl compounds according to claim 1, wherein the sum of the pore volume Vp(BJH) calculated by the BJH method and the pore volume Vp(MP) calculated by the MP method is 0.40 mL / g or more and 2.00 mL / g or less, and the proportion of Vp(BJH) in the sum of Vp(BJH) and Vp(MP) is 50% or more.

3. 3. The adsorbent for perfluoroalkyl and polyfluoroalkyl compounds according to claim 1 or 2, wherein the content of magnesium oxide is 15 mass% or more.

4. A method for producing an adsorbent for perfluoroalkyl and polyfluoroalkyl compounds, comprising the steps of mixing a magnesium oxide precursor, an aluminum oxide precursor, and water to granulate the mixture, and calcining the granulate.

Citation Information

Patent Citations

  • Filter medium for removing perfluorooctane sulfonate from water and preparation method thereof

    CN101992061A

  • Preparation method of porous electropositive fly ash adsorbent

    CN113893828A

  • Magnetic recording and reproducing device

    JP1986043089A

  • Perfluoroalkyl and polyfluoroalkyl adsorbent materials and methods of use

    JP2022526606A

  • Adsorption filter, filter for plating solution purification using same, plating solution purification device and plating solution purification method

    WO2021085266A1

Cited By

  • Method for utilizing zeolite related to PFAS and apparatus directly used for its implementation, and method for manufacturing amorphous materials related to PFAS and apparatus directly used for its implementation.

    JP7900802B1